Development of smart logistic framework for blood donor information system based on Internet of Things - Yulistiyanto , Mohamad Tri Angga; Mansur, Agus; Nur Cahyo, Winda; Ramadhan, Fadhil Adita (OPSI, 2025)
In 2021, the amount of blood production by the Indonesian Red Cross was higher than the existing needs. This can result in wasted blood bags. The availability of abundant blood bag supplies is not balanced with access to information on the availability of these blood bags. This study aims to build a smart logistics system that can provide information on the availability of blood bags in real-time. This study utilized a quantitative and explorative approach and employed the waterfall Software Development Life Cycle (SDLC) method using PHP and the CodeIgniter 3 framework, which was integrated with IoT devices such as sensors and GPS for real-time monitoring. In addition, this system will provide a tool to predict the number of donors needed, as well as estimate the number of donor quotas required during upcoming blood donation activities. This study has succeeded in developing a blood donor information system that adopts the smart logistics concept to control blood bag stock. The resulting system is capable of reducing the risk of shortages and obsolescence while enhancing synergy among stakeholders. The design of a system that facilitates openness of information on the level of blood needs and simplification of the donor system is expected to increase community responsibility in creating sustainable blood supply availability.